Post-Last Glacial Maximum expansion from Iberia to North Africa revealed by fine characterization of mtDNA H haplogroup in Tunisia - Cherni, L (2009)
The first large-scale fine characterization of Tunisian H lineages clarifies that the post-Last glacial maximum expansion originating in Iberia not only led to the resettlement of Europe but also of North Africa. We found that 46% of 81 Tunisian H lineages subscreened for 1,580 bp in mtDNA coding region were affiliated with H1 and H3 subhaplogroups, which are known to have originated in Iberia. Although no signs of local expansion were detected, which would allow a clear dating of their introduction, the younger and less diverse Tunisian H1 and H3 lineages indicate Iberia as the radiating centre. Major contributions from historical migrations to this Iberian genetic imprint in Tunisia were ruled out by the mtDNA gene pool similarity between Berber/Arab/cosmopolitan samples and some "Andalusian" communities, settled by the descendents of the "Moors" who once lived in Iberia for 10 centuries (between 8th and 17th centuries), before being expelled to Tunisia.